Elevated cerebrospinal fluid cytokine levels in tuberculous meningitis predict survival in response to dexamethasone - Whitworth, Laura J. (Proc Natl Acad Sci U S A, 2021)
Adjunctive treatment with antiinflammatory corticosteroids like dexamethasone increases survival in tuberculosis meningitis. Dexamethasone responsiveness associates with a C/T variant in Leukotriene A4 Hydrolase (LTA4H), which regulates expression of the proinflammatory mediator leukotriene B(4) (LTB(4)). TT homozygotes, with increased expression of LTA4H, have the highest survival when treated with dexamethasone and the lowest survival without. While the T allele is present in only a minority of the world’s population, corticosteroids confer modest survival benefit worldwide. Using Bayesian methods, we examined how pretreatment levels of cerebrospinal fluid proinflammatory cytokines affect survival in dexamethasone-treated tuberculous meningitis. LTA4H TT homozygosity was associated with global cytokine increases, including tumor necrosis factor. Association between higher cytokine levels and survival extended to non-TT patients, suggesting that other genetic variants may also induce dexamethasone-responsive pathological inflammation. These findings warrant studies that tailor dexamethasone therapy to pretreatment cerebrospinal fluid cytokine concentrations, while searching for additional genetic loci shaping the inflammatory milieu.